1995
DOI: 10.1063/1.871422
|View full text |Cite
|
Sign up to set email alerts
|

Ion-acoustic solitons in electron–positron–ion plasmas

Abstract: The ion-acoustic solitons are investigated in three-component plasmas, whose constituents are electrons, positrons, and singly charged ions. It is found that the presence of the positron component in such a multispecies plasma can result in reduction of the ion-acoustic soliton amplitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
278
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(294 citation statements)
references
References 12 publications
14
278
2
Order By: Relevance
“…Positrons are produced by pair production in high energy processes occurring in many astrophysical environments. Popel et al [9] have reported decrease in soliton amplitude in the presence of positrons. Jehan et al [13] have shown that solitons become narrower as the concentration of positron increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positrons are produced by pair production in high energy processes occurring in many astrophysical environments. Popel et al [9] have reported decrease in soliton amplitude in the presence of positrons. Jehan et al [13] have shown that solitons become narrower as the concentration of positron increases.…”
Section: Introductionmentioning
confidence: 99%
“…For this, over the last two decades there has been a great deal of interest in the study of nonlinear wave phenomena in --plasmas [8][9][10][11][12]. Positrons are produced by pair production in high energy processes occurring in many astrophysical environments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore to obtain a good agreement with experiments, in this method, one needs to take higher-orders in perturbation amplitudes. In recent years there have been many investigations on solitary IASWs as well as solitary electrostatic waves (ESWs) in diverse plasma environments using Sagdeev pseudo-potential approach [9][10][11][12][13]. The small amplitude propagation and interaction of IASWs with relativistic degeneracy pressure effects have been recently considered in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Popel et al [23] considered the nonlinear propagation of IA waves in cold plasma consisting of cold ions, and isothermally distributed electrons and positrons. They have found the existence of compressive solitons only.…”
Section: Introductionmentioning
confidence: 99%